Effectiveness of perform+ training program for ankle injury at Academy Nazzaro Football Club Malang - Damayanti, Dita Angelia; Abdullah, Ahmad; Pribadi, Heri Purnama (CV. Media Digital Publikasi Indonesia, 2023)
One of the most common injuries in soccer is an ankle injury, which has a prevalence of injury of 41.1%. To prevent ankle injuries in soccer, a training program such as Performance+ Football Australia is needed because this program is effective in reducing the injury rate by around 40%. Therefore, the researchers aim to implement this training program in Indonesia to determine the effectiveness of preventing ankle injuries in Indonesia soccer players. The type of this research uses a pre-experimental design by using one-group pretest-posttest design research with one group given the perform+ training program treatment. The subjects used in this study are teenage male soccer players who are members of Nazzaro Football Club Academy Malang, with a sampling technique using purposive sampling based on inclusion criteria and obtained 15 research samples given the perform+ training program to present ankle injuries. The perform+ training program is carried out for 6 weeks with a frequency of 3 training sessions per week. to determine the effectiveness of the perform+ training program, the Y Balance Test is used. The analysis used in this study uses normality test analysis and hypothesis testing with the help of SPSS 21. The results show that the composite pretest value of the range of right and left legs obtained a Y Balance t-test result of 0,000 which means that the significance value is <0.05, indicating a significant effect. Based on the data analysis above with t-test results, it can be concluded that there is an effectiveness of the perform+ training program for the Nazzaro Football Club Academy Malang Players.